The geography of same-sex couples and families in Australia: an empirical review. Issue 4 (2nd October 2019) - Forrest, James; Gorman-Murray, Andrew; Siciliano, Frank
ABSTRACT: Much has changed since the first mapping of single-sex couples and families from the 2006 Australian census. An increasing willingness to allow their identification in the census has accompanied increasing public acceptance of same-sex couples culminating in significant support for legalising same-sex marriage in a 2017 national survey. Technological advances permit complex cross-tabulations of Australian census data and more detailed characterisations of same-sex couples. New geographies differentiate between male and female couples with children, showing same-sex couples are not just a feature of some inner-city areas, though these remain important, but also of suburban, regional and some rural areas. Drawing on the 2016 census, contemporary geographies of same-sex couples with and without children in Australia and changes over the past decade in Sydney are analysed at a time of increased interest in this demographic.